2006
DOI: 10.1029/2006gl025934
|View full text |Cite
|
Sign up to set email alerts
|

Observations of amplitude saturation in ELF/VLF wave generation by modulated HF heating of the auroral electrojet

Abstract: We present detailed observations of the onset of amplitude saturation in ELF/VLF waves generated via modulated HF heating of naturally‐forming, large‐scale current systems, such as the auroral electrojet. Broadband ELF/VLF measurements at a ground‐based receiver located near the High‐Frequency Active Auroral Research Program (HAARP) HF transmitter in Gakona, Alaska, exhibit variations in signal amplitude which are qualitatively consistent with a hard‐limiting approximation of the saturation process. A method t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 7 publications
0
48
0
2
Order By: Relevance
“…The HF heating component of the model is described in detail by Cohen et al [2010a] and builds off the work of Tomko et al [1980], Rodriguez [1994], Payne [2007], and Moore [2007]. To summarize, the three‐dimensional model uses a grid, which in this case is defined from 60–95 km in altitude and spans 160 km in each horizontal direction.…”
Section: Theoretical Modelingmentioning
confidence: 99%
“…The HF heating component of the model is described in detail by Cohen et al [2010a] and builds off the work of Tomko et al [1980], Rodriguez [1994], Payne [2007], and Moore [2007]. To summarize, the three‐dimensional model uses a grid, which in this case is defined from 60–95 km in altitude and spans 160 km in each horizontal direction.…”
Section: Theoretical Modelingmentioning
confidence: 99%
“…A most unexpected result revealed by the simulations is the distribution of the ELF magnetic amplitude on the ground signatures as a function of distance from the heater, shown in Figure 9. Previous experience with ELF and ULF waves generated by modulating the Polar Electrojet (PEJ) [ Rietveld et al , 1984, 1987, 1989; Papadopoulos et al , 1990, 2005; Moore , 2007; Payne et al , 2007] indicated that the wave amplitude had a maximum in the vicinity of the heater while monotonically decreasing with distance in a fashion consistent with guided wave propagation. However, as noted in Section 3.3, ICD driven waves have a minimum at the ground location defined by its interception with the magnetic field line that passes through the heated volume.…”
Section: Some Experimental Resultsmentioning
confidence: 99%
“…The dynamics of the plasma is then governed by the inertia‐less electron momentum equation and the ion momentum equation boldvit=emi(E+boldvi×boldB0)vitalicinboldvi, where m e and m i are the electron and ion masses, v en and v in are the electron‐neutral and ion‐neutral collision frequencies, and P e is the externally modulated electron pressure, which provides the source of ELF/ULF electromagnetic waves. The model does not take into account nonlinearities associated with HF wave propagation through the D‐region, frequently used to generate ELF and ULF waves by modulating the Polar Electrojet (PEJ) [ Rietveld et al , 1984, 1987, 1989; Papadopoulos et al , 1990, 2005; Moore , 2007; Payne et al , 2007]. We have assumed that collisions with neutrals are dominant.…”
Section: The Ionospheric Modelmentioning
confidence: 99%
“…Previous results with ELF and ULF waves generated by modulating the polar electrojet (PEJ) [Rietveld et al, 1984[Rietveld et al, , 1987[Rietveld et al, , 1989Papadopoulos et al, 1990Papadopoulos et al, , 2005Moore, 2007;Payne et al, 2007] indicated that the wave amplitude had a maximum in the vicinity of the heater while monotonically decreasing with distance in a fashion consistent with guided wave propagation. In general, ICD driven waves have a minimum at the ground location defined by its intersection with the magnetic field line that passes through the heated volume.…”
Section: Waves Generated By Modulated Hf Heating: Ionospheric Currentmentioning
confidence: 96%